Temperature effect on hidration reaction of α-pinene to α-terpineol catalyzed by activated nature zeolite) - Nia Amilia; Kusoro Siadi; Latifah Latifah (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2013)
system over activated nature zeolite has been conducted. The purposes of the research are toknow the best temperature of hydration reaction α-pinene to α-terpineol using activated naturezeolite and to determine the value of activation energy for the hydration reaction. Characterizationof the catalyst include surface area, pore size, and pore volume was performed using GasSorption Analyzer NOVA1200e. Reaction occurs at various temperature of 30, 40, 50, 60, 70, and80oC. The product of reaction is analyzed using infra red spectroscopy, gas chromatography, andchromatography-mass spectroscopy for the best product. Results of the analysis using infra redshow absorption of OH group at 3400cm-1, C-H at 2987,09cm-1, C=C bond at 1635,64cm-1, andC-O at 1126,43 cm-1. Effect of increasing temperature influences the convertion (%) α-pinene toα-terpineol. The best result was reached at 70oC for 68.53% and the activation energy of reactionhydration is 69.6546 kJmol-1.Key words: α-pinene, temperature, hydration reaction, α-terpineol